Analisis Kemampuan Ketrampilan Dasar Mengajar Guru Bagi Mahasiswa Pendidikan Biologi Pengampu Mata Kuliah Mikroteaching STKIP YPM Bangko - Arista Ratih (BIOCOLONY, 2018)
Mikroteaching is a compulsory course that must be addressed by biology education students in the curriculum of KKNI. This course is followed by students of semester VII. In the implementation of microteaching, students will be taught first how to develop RPP (learning implementation plan) and material about basic skill of teaching teacher. This teacher's basic teaching skill consists of: open learning skills, closing lesson skills, material explaining skills, strengthening skills, small and large group coaching skills, classroom management skills, variation in learning, and questioning skills. The method in this research is direct observation by observing the students who practice teaching in front of the class which is analyzed by quantitative descriptive method. Its population is 61 people and sample 23 people. Based on the result of the research, it is found that the average of basic skill of good teacher teaching.